Optimization of Wheat and Barley Production under Changing Climate in Rainfed Pakistan Punjab - A Crop Simulation Modeling Study - Aziz, Marjan; Tariq, Muhammad; Ishaque, Wajid (Annals of Arid Zone, 2017)
Rainfed agriculture is extremely vulnerable to climate change. Climate change is both an opportunity and a potential threat to future agriculture and livestock production globally and in Pakistan particularly. Impacts of climate change will have significant reflections on field practices of wheat growers. The present study is mainly directed to discuss sensitivity of climate change upon the wheat and barley production in rainfed areas of Pakistan Punjab. Field experiments were conducted at Barani Agricultural Research Institute, Chakwal during winter seasons of 2014 and 2015 to study the effects of sowing date and three irrigation levels on grain yield and its attributes of wheat (Triticum aestivum) cultivar Chakwal-50 and barley (Hordeum vulgare) cultivar Joe-83. Experimental conditions and results obtained from the location were used as a database for calibration (2010, 2012 and 2013) and experiments were performed in 2014-2015 for validation of CERES-wheat and CERES-barley models of DSSAT4.5 package to study the sensitivity of climate change on wheat and barley growth and yield. Results show that by comparing results obtained from CERES-wheat and CERES-barley model and actual observations in the field enabled us to reach very good calibration (anthesis (DAP) RMSE = 3 and 3, NRMSE = 2% and 3%, dstat = 0.84 and 0.783 and r square = 0.98 and 0.75; physiological maturity (DAP) RMSE = 3 and 4, NRMSE = 2 and 3%, d-stat = 0.9 and 0.843, r square = 0.98 and 0.82; grain yield (kg ha-1) RMSE = 173 and 174, NRNSE = 4% and 13%, d-stat = 0.68 and 0.737, r square = 0.75 and 0.99, respectively) and validation (anthesis (DAP) RMSE = 2 and 3, NRMSE = 2% and 3%; physiological maturity (DAP) RMSE = 2 and 3, NRMSE = 1 and 2%; grain yield (kg ha-1) RMSE = 195 and 192, NRNSE = 5% and 24%, respectively) of the model for predicting phonological stages as well as grain yield at different locations using different treatments. Scenario simulations showed that optimum sowing date for wheat and barley was 20-30 November and 25 November to 5 December, respectively, and in case of dry year 30 mm supplemental irrigation could be applied at the time of sowing or 30 DAS.